The Effect Of Compensation And Job Insecurity On Employee Loyalty Through Working Relationship As An Intervening Variable (Case Study Of Manufacturing Employees In Jababeka Bekasi ) - Hikmah, Mia Aulia; Bimanti Esthi, Raniasari (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose - The purpose of this study was to examine the effect of compensation and job insecurity on employee loyalty with work relationships as intervening variables in the Jababeka Bekasi manufacturing company. Novelty - This study presents a new approach by placing work relationship variables as mediating variables in explaining the impact of compensation and job insecurity on employee loyalty, especially in the manufacturing industry environment in the Jababeka Bekasi area, which has not been widely revealed in previous studies. Method - This study uses a quantitative approach with 171 respondents as a sample. Data were collected through observation, literature studies and questionnaires that have been tested through validity and reliability tests. The analysis was carried out using the PLS-SEM version 3.0 analysis method. Findings -.The results show that compensation has a significant effect on the employment relationship, while job insecurity does not show a significant effect on the employment relationship. In addition, compensation does not have a significant direct effect on employee loyalty, while job insecurity has a significant effect on loyalty. Job relations proved to act as a significant mediating variable in strengthening the effect of compensation on employee loyalty. However, the employment relationship is not able to mediate the relationship between job insecurity and employee loyalty. Limitations and Implications The limitations of this study lie in the use of survey methods that rely on subjective perceptions of respondents, so they have the potential to cause bias. Therefore, the variable of work relationship as an intervening variable has only been tested in a limited context, so its consistency in other sectors cannot be ascertained. Companies must prioritize the quality of work relationships as an essential element in strengthening and reducing the impact of job insecurity on employee loyalty. HR managers must create a supportive, communicative, and collaborative work environment to increase employee retention in the long term.